The Influence Of Learning In Using Educational Video And CTPS Gymnastic Learning (Covid-19) On Hand Washing Implementation By Using Soap Under Flowing Water - Sudirman Burhanuddin; Nur Amalia Saenal (UNIVERSITAS NEGERI MAKASSAR, 2022)
This type of research is an experiment that aims to improve the culture of washing hands with soap under running water for students at SD Muhammadiyah IDI Tello Baru in Makassar City. The population of the study were students at SD Muhammadiyah IDI Tello Baru in Makassar City. The sample was selected by using simple random sampling technique and obtained 60 people. The data analysis technique employed a sample paired t test and an independent t test. The results of the study reveal that there is an influence of learning using educational videos on the culture of washing hands with soap under running water for students at SD Muhammadiyah IDI Tello Baru in Makassar City with a value of Sig. (2- tailed) of 0.000 < 0.05 or H0 is rejected. There is an influence of learning CTPS (Covid-19) gymnastics on the culture of washing hands with soap under running water for students at SD Muhammadiyah IDI Tello Baru in Makassar City with a value of Sig. (2-tailed) of 0.000 < 0.05 or H0 is rejected. There is a difference between learning using educational videos and learning CTPS (Covid-19) gymnastics on the culture of washing hands with soap under running water for students at SD Muhammadiyah IDI Tello Baru in Makassar City with a value of t = 2.150 and Sig. (2-ailed) = 0.038 < 0.05 or H0 is rejected.